The Christology of the Fourth Gospel Its Unity and Disunity in the Light of John 6 - Anderson, Paul N. (Mohr Siebeck, 1996)
The Christology of the Fourth Gospel. Its Unity and Disunity in the Light of John 6
PublicationDate: 20191210
Keywords: Johannesevangelium -- Neues Testament -- Array